Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Aritmatika Sosial (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to describe students' critical thinking skills in solving social arithmetic problems based on the Polya stages and FRISCO indicators. The research subjects consisted of three students in grade VIII R-5 MTs Nurul Jadid who were purposively selected to represent the high, medium, and low ability categories out of a total of 21 students. The research method used was a descriptive qualitative approach with instruments in the form of two social arithmetic description questions and semi-structured interview guidelines. Data analysis was carried out by referring to the four stages of problem solving according to Polya (understanding the problem, planning the solution, executing the plan, and re-examination) as well as the six FRISCO critical thinking indicators (Focus, Reason, Inference, Situation, Clarity, Overview). The results of the study showed that students with high abilities were able to solve problems systematically through all stages of Polya and met almost all FRISCO indicators, especially in the aspects of Focus, Reason, and Clarity. Students with moderate ability show sufficient understanding but are inconsistent in planning and implementing solutions, and experience difficulties in the Reason, Situation, and Overview indicators. Students with low abilities experience obstacles from the early stages of understanding problems and do not show significant indicators of critical thinking. These findings indicate that the Polya stage and the FRISCO indicator can be used in a complementary manner to identify and analyze students' critical thinking skills in solving contextual math problems. The implication of this study is the need for a learning strategy that emphasizes strengthening the stages of problem solving and developing explicit critical thinking indicators in the mathematics learning process. This research also opens up opportunities for the development of more structured diagnostic instruments in measuring students' individual critical thinking skills.